PERANAN STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN DI THE EXCELTON HOTEL PALEMBANG (Universitas Muhammadiyah Palembang, 2022)
Purpose. The purpose of the research was to determine what marketing strategy is considered the best to use in increasing sales volume at The Excelton Hotel Palembang. The data analysis used in this research is qualitative analysis. The scope of this research is the role of marketing strategy which includes Product, Price, Place, Promotion, People, Process, and Physical Evidence.Based on the research results, The Excelton Hotel Palembang products, especially in rooms, food, drinks, and meeting rooms/ballrooms, have a 5-star standardization certificate so they are very suitable for use by every guest. Prices set by management for rooms, food, drinks, and meeting rooms/ballrooms, are comparable to competitors prices in accordance with the quality of the products provided at competitive prices in the market. The strategic location and the selection of the best spot also make The Excelton Hotel Palembang has its own charm. The Excelton Hotel Palembang carried out several promotional strategies, including advertising, Personal selling, Sales Promotion, and Public Relations. The employees who work at The Excelton Hotel Palembang have the ability and skills in their respective fields. And equipped with some more expertise so as to produce maximum products/services. The process used at The Excelton Hotel Palembang has met the 5-star standard so that the SOP can run according to the rules that have been set. The physical evidence applied by The Excelton Hotel Palembang have charms ranging from the shape of the building, logo selection, to a simple but elegant interior.